Strengthening Islamic Values in the Family through Artificial Intelligence (AI)-based Learning Technology - Azzahroh, Husna Syifa'; Salim, Hakimuddin (Universitas Muhammadiyah Surakarta, 2025)
The purpose of this article is to explore the potential use of AI-based Islamic learning technology as a tool for parents to instill and reinforce Islamic values within the family. This research utilizes a qualitative method with data obtained from a literature review. The literature review was conducted by collecting various relevant data from sources such as academic journals, books, and online materials, which were then analyzed in-depth to formulate an accurate conclusion. In this context, AI offers various innovative features, such as virtual assistants, interactive applications, and personalized content, which can simplify the task of providing religious guidance to children.The results of the study show that AI-based technology can be a highly effective tool in supporting parents to guide children interactively, strengthen their understanding of religious teachings, and foster emotional closeness within the family. The utilization of this technology demonstrates that technological development can bring not only negative but also positive impacts if used wisely. This article also provides practical recommendations on how to optimally utilize AI without ignoring the essence of Islamic teachings. Thus, it is hoped that technology can help in shaping a generation with a strong religious foundation, noble character, and resilience in facing global challenges.